Identifikasi Thrips alliorum (Priesner), Thrips hawaiiensis (Morgan), dan Thrips parvispinus (Karny) berdasarkan variasi DNA COI mitokondria - Nia Kurniawaty; Purnama Hidayat; Aunu Rauf (Jurnal Entomologi Indonesia, 2017)
Thrips is the second largest genus on the order of Thysanoptera, most of them are polyphagous and some species are serious pests on vegetables. The damages caused by thrips can reach 30–50% yield loss. Thrips alliorum (Priesner), T. hawaiiensis (Morgan), and T. parvispinus (Karny) are widely reported as pests on crops, especially on horticulture. This study aimed to identify three trhips species: Thrips alliorum, T. hawaiiensis, and T. parvispinus based on the DNA sequences of mtCOI gene fragment. Thrips samples were collected from Bandung, Bogor, Cianjur, and Kuningan districts. Three steps, they were sample collection and DNA total extraction, amplification by using PCR and DNA sequence analysis. The PCR succesfully amplified DNA of mtCOI gene fragments of T. alliorum, T. hawaiiensis, and T. parvispinus at 678, 690, and 668 bp respectively. The mtCOI DNA sequences were dominated by A and T bases with the nucleotide variation value of  25.18%. Identification of the three thrips species: T. alliorum, T. hawaiiensis, and T. parvispinus based on molecular characters using mtCOI DNA sequences confirmed the identification result based on the morphological caharacters.